2007
DOI: 10.1007/s10651-007-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

External drift kriging of NOx concentrations with dispersion model output in a reduced air quality monitoring network

Abstract: In the mid nineteen eighties the Dutch NO x air quality monitoring network was reduced from 73 to 32 rural and city background stations, leading to higher spatial uncertainties. In this study, several other sources of information are being used to help reduce uncertainties in parameter estimation and spatial mapping. For parameter estimation, we used Bayesian inference. For mapping, we used kriging with external drift (KED) including secondary information from a dispersion model. The methods were applied to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…KED implementation follows Van de Kassteele et al (2009) that combine observations and deterministic dispersion model data of atmospheric NO x concentration. Specifically, the kriging is applied on the observed data and the external drift is constituted by the deterministic model output.…”
Section: Data Description and Preprocessingmentioning
confidence: 99%
“…KED implementation follows Van de Kassteele et al (2009) that combine observations and deterministic dispersion model data of atmospheric NO x concentration. Specifically, the kriging is applied on the observed data and the external drift is constituted by the deterministic model output.…”
Section: Data Description and Preprocessingmentioning
confidence: 99%
“…They illustrate RK for predicting a hard‐to‐measure soil variable, nitrous oxide (N 2 O) emissions from the soil: the RK predictions are based on direct measurements of the N 2 O emissions and a process model for the emissions, given data on more readily measured input variables for this model. They show that this approach gives better estimates than those from either the process model or geostatistical prediction from data separately; other RK case studies have drawn similar conclusions (Maxwell et al , 2009; van de Kassteele et al , 2009).…”
Section: Introductionmentioning
confidence: 65%
“…An earlier study using a comparable data set of NO x concentrations (Van de Kassteele et al, 2005) showed that a large part of the variation in the observations could be explained by the OPS output. This resulted in a high value for the range parameter ($ 1000 km), leading to an almost linear shape of the exponential correlation function on the Dutch scale.…”
Section: No 2 Concentrations In the Netherlandsmentioning
confidence: 99%
“…In the Netherlands, 45 NO 2 monitoring stations, to which secondary information is added from a highresolution dispersion model, are used for this purpose. Kriging with external drift (KED) has been shown to be useful in merging these two sources of information (Van de Kassteele et al, 2005). The primary variable, given by the monitoring data, is combined with a secondary variable, the dispersion model output, as the external drift covering the whole domain.…”
Section: Introductionmentioning
confidence: 99%